The Effect of Using Kahoot! Game in Teaching English to Improve Students’ Reading Comprehension - Galina Sitinjak; Nenni Triana Sinaga; Sahlan Tampubolon (Institute of Computer Science (IOCS), 2022)
This article is based on the author's initial observations through interviews with students of English Education Study Program, HKBP Nommensen Medan. Researchers found several problems in achieving student reading comprehension, especially in third-semester students. This research method is descriptive qualitative, which aims to collect and describe information related to answers from respondents given to students through questionnaires and interviews. The subjects in this study were students in the third semester of English education at the University of HKBP Nommensen Medan. The sample in this study was 31 students. The results of this study indicate that 89% of students agree with Kahoot! Games are learning media that are easy to access and easy to use when learning English to improve students' reading comprehension, and 70% agree that Kahoot! Games are useful for students because they can help students explore English reading material delivered by lecturers.